Iqra' as Knowledge Paradigm: Islamic Epistemology Reconstruction from QS Al-Alaq 1-5 - Hartono, Hartono; Ismail (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2026)
This study reconstructs Islamic epistemology by positioning the Qur'anic command